Eccrine Spiradenoma in a Male of 33 Years Old: A Case Report - Flores-López, Alejandro Alberto; García-Flores, Rubén; Ucán-Gamboa, Dioney Josimar; Solís-Reyna, Víctor Hugo; Figueroa-Araujo, Demian; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: Eccrine spiradenoma is a rare benign neoplasm first described by Kersting and Helwig in 1956. It arises from sweat glands in the dermis and superficial subcutaneous tissue. There is usually no connection to the overlying epidermis. It can occur at any age but more commonly affects young adults and has no sexual predilection. Most patients present with pain or tenderness, as observed in 91% of patients. Clinical Case: A 33-year-old male was referred from his family medicine clinic for a probable epidermal cyst on the right forearm with no history of importance for the case that began six years ago with a papule with progressive growth and pain to the touch; later, he presented cessation of treatment. The patient tried to remove it himself without success, so he went to this hospital for exeresis; the sample it sent for a histopathological study, which reported: A dermoid tissue fragment of 0.4x0.2x0.2, grayish brown in color and firm consistency. In the sections, neoformations composed of homogeneous cubic cells with ovoid and hyperchromatic nuclei with ductal zones and observed empty spaces. Histopathological diagnosis of eccrine spiroadenoma. Discussion: Spiroadenomas are well-differentiated, benign, dermal neoplasms arising from the hair follicle’s pons rather than the eccrine sweat gland, based on CD200 and stem cell marker immunohistochemical study. The pathogenesis is not fully understood, but a defect in the tumor suppressor gene, CYLD, is believed to contribute to its development in Brooke-Spiegler syndrome, which also presents multiple spiradenomas.